Life Cycle Assessment of Indonesian Traditional Chicken Satay with Peanut Sauce - Yosef Barita Sar Manik; Ignatius David Fernando; Chandra Aden Akbar Pamungkas; Diogo Anibal; Jovian Nathan Sutedja (School of Postgraduate Studies, Diponegoro Univer, 2026)
This study applies the Life Cycle Assessment (LCA) method to evaluate the environmental impact of traditional Indonesian chicken satay production with peanut sauce. Using a gate-to-gate approach, the research covers raw material acquisition, preparation, and cooking. The analysis follows ISO 14040 and ISO 14044 standards, utilizing OpenLCA software and the Agribalyse_V3.0.1 database. The functional unit is defined as 10 servings of chicken satay based on a recipe from an article on Indonesian cultural food products and food safety tips. The inventory includes input materials such as chicken, peanuts, spices, cooking oil, and energy and water consumption. Outputs include emissions, wastewater, and solid waste. The ReCiPe 2016 (H) midpoint method is used to assess key environmental impacts, including Global Warming Potential (9.41E+00 kg kg CO₂ eq), Ozone Depletion (6.29E-05 kg CFC-11 eq), Human Toxicity (1.65E-01 kg 1,4-DCB), Fine Particulate Matter Formation (1.78E-02 kg PM2.5 eq), Acidification (8.69E-02 kg SO₂ eq), and Eutrophication (1.24E-02 kg N eq). The results show that the largest impact comes from raw material production, particularly poultry farming and peanut cultivation, as well as high energy consumption during cooking. Impact reduction strategies include fuel efficiency, sustainable raw material selection, and food waste reduction. This study provides valuable insights into supporting the sustainability of traditional Indonesian cuisine and improving a more environmentally friendly food production system.